2011
DOI: 10.1007/s11069-011-9772-1
|View full text |Cite
|
Sign up to set email alerts
|

Ground motion studies for microzonation in Iran

Abstract: An important step in effectively reducing seismic risk and the vulnerability of a city located in an earthquake prone area is to conduct a ground motion microzonation study for the desired return period. The International Institute of Earthquake Engineering and Seismology (IIEES) initiated a number of seismic microzonation projects for Iran. This paper presents the steps followed by IIEES in ground motion microzonation. IIEES performs both probabilistic and deterministic seismic hazard analysis. IIEES uses his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A damped linear elastic model of the soil system is used for the analysis. Due to soil nonlinearity for which the shear modulus is strain dependent, ProShake performs an iterative process on the linear model until both the moduli and damping ratios are compatible with the average strains and convergence is achieved at the last iteration (Shafiee et al, 2011;Puri et al, 2018). The nonlinear and hysteretic stress-strain behavior of soils under cyclic .…”
Section: Geotechnical Site Characterizationmentioning
confidence: 99%
“…A damped linear elastic model of the soil system is used for the analysis. Due to soil nonlinearity for which the shear modulus is strain dependent, ProShake performs an iterative process on the linear model until both the moduli and damping ratios are compatible with the average strains and convergence is achieved at the last iteration (Shafiee et al, 2011;Puri et al, 2018). The nonlinear and hysteretic stress-strain behavior of soils under cyclic .…”
Section: Geotechnical Site Characterizationmentioning
confidence: 99%
“…Similarly, the Earthquake Model of Middle East (EMME) project (Şeşetyan et al 2018) developed in 2014 a regional scale harmonized seismic hazard model for eleven countries in the Middle East region (Danciu et al 2016b). At the urban level, many studies have focused on the seismic hazard analysis of large cities such as Tehran, Shiraz, Mashhad and Qom (Abdi et al 2013;Ghodrati Amiri et al 2008;Jafari et al 2005;Kamalian et al 2008;Sadeghi et al 2014;Shafiee et al 2011;Zafarani et al 2017). Two studies investigated the seismic hazard of Isfahan in terms of characterization of the active faults around the city (Beygi et al 2016;Safaei et al 2012) and to generate a micro-zonation PGA hazard map (Tajmir Riahi et al 2014).…”
Section: Existing Hazard and Risk Assessment Studies For Iranmentioning
confidence: 99%
“…The first relevant applications appeared in USA and Japan in the early 1970s [21], whereas during the ten years that followed the first applications, a number of microzonation conferences (Seattle 1972, San Francisco 1978, Seattle 1992, Nice 1995) played a significant role in advancing the level of knowledge on the subject. During the past three decades the field of applied research on seismic microzonation has received a continuously increasing attention with the emphasis put to applications concerning urban areas of varying size, ranging from mega-cities to smaller cities or towns [4][5][6]24,44,43,20,14,28,[57][58][59]2,15,21,23,46,61,27]. Yasuda et al [62] have recently demonstrated the reliability of a carefully planned microzonation study in Japan by comparing the actual damage observed in the 2005 Fukuoka -Ken Seiho -Oki earthquake to the predictions of a microzonation study that was conducted 7 years before the occurrence of the earthquake.…”
Section: Introductionmentioning
confidence: 99%